Be prepared - Brosgol, Vera. (New York : First Second, 2018)
"All Vera wants to do is fit in--but that's not easy for a Russian girl in the suburbs. Her friends live in fancy houses and their parents can afford to send them to the best summer camps. Vera's single mother can't afford that sort of luxury, but there's one summer camp in her price range--Russian summer camp. Vera is sure she's found the one place she can fit in, but camp is far from what she imagined. And nothing could prepare her for all the 'cool girl' drama, endless Russian history lessons, and outhouses straight out of nightmares!"--Amazon.com.
Booklist starred
Bulletin (Center for Children's books)
Horn Book Starred
Booklist starred, April 2018
Bulletin (Center for Children's books), April 2018
Horn Book Starred, May 2018
Keywords: Brothers and sisters -- Comic books, strips, etc. -- Juvenile fiction; Camps -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Russian Americans -- Comic books, strips, etc. -- Juvenile fiction; Social acceptance -- Comic books, strips, etc. -- Juvenile fiction; Brothers and sisters -- Fiction; Camps -- Fiction; Friendship -- Fiction; Russian Americans -- Fiction; Social acceptance -- Fiction; Camps -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Russian Americans -- Comic books, strips, etc. -- Fiction; Siblings -- Comic books, strips, etc. -- Fiction; Social acceptance -- Comic books, strips, etc. -- Fiction; Graphic novels